2019
DOI: 10.1063/1.5079441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular size and hydrogen bonding on three surface-facilitated processes in molecular glasses: Surface diffusion, surface crystal growth, and formation of stable glasses by vapor deposition

Abstract: Recent work has shown that diffusion and crystal growth can be much faster on the surface of molecular glasses than in the interior and that the enhancement effect varies with molecular size and intermolecular hydrogen bonds (HBs). In a related phenomenon, some molecules form highly stable glasses when vapor-deposited, while others (notably those forming extensive HBs) do not. Here we examine all available data on these phenomena for quantitative structure-property relations. For the systems that form no HBs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 52 publications
(50 reference statements)
2
26
0
Order By: Relevance
“…In general, measured D s values on organic glasses range from 10 -11 to 10 -16 m 2 /s at T g , 4 to 8 orders of magnitude larger than the bulk counterpart, as shown in Fig. 8 This eightfold enhancement of surface diffusion with respect to bulk diffusion [131] allows to circumvent the restrictions to molecular rearrangement imposed by the slow bulk dynamics. Indeed, at the surface layer, molecules exhibit diffusion levels that allow them to reach stable packing arrangements in timescales comparable to the residence time of these molecules on the surface.…”
Section: Is Surface Diffusion Responsible For Ultrastable Glass Forma...mentioning
confidence: 94%
See 2 more Smart Citations
“…In general, measured D s values on organic glasses range from 10 -11 to 10 -16 m 2 /s at T g , 4 to 8 orders of magnitude larger than the bulk counterpart, as shown in Fig. 8 This eightfold enhancement of surface diffusion with respect to bulk diffusion [131] allows to circumvent the restrictions to molecular rearrangement imposed by the slow bulk dynamics. Indeed, at the surface layer, molecules exhibit diffusion levels that allow them to reach stable packing arrangements in timescales comparable to the residence time of these molecules on the surface.…”
Section: Is Surface Diffusion Responsible For Ultrastable Glass Forma...mentioning
confidence: 94%
“…Enhanced molecular diffusion at the surface is responsible for fast surface crystal growth in many organic glasses as crystal growth rate is nearly proportional to the surface diffusion coefficient, D s [130]. One way to measure surface diffusion is by the embossing of surface gratings onto glassy surfaces and subsequent measurement by diffraction of the decay of the grating pattern [89,131]. Surface diffusion can also be accessed by measuring the evolution of the response when a probe is placed on the surface, inducing the formation of a meniscus due to surface-mediated flow.…”
Section: Is Surface Diffusion Responsible For Ultrastable Glass Forma...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that surface diffusion of molecular glasses can be strongly affected by several factors, including strength of molecular interaction [47,48], molecular size [49], and the addition of polymer [43]. With the increase in the strength of molecular interaction and molecular size, surface diffusion of amorphous solids exhibits a tendency to slow down [47][48][49][50][51]. For instance, Chen et al found that the surface diffusion of polyalcohol glasses showing extensive hydrogen bonding is much slower than that of the molecular glasses of comparable size but with no or limited hydrogen bonds [48].…”
Section: Surface Grating Decay and Surface Diffusionmentioning
confidence: 99%
“…The existence and extent of intermolecular hydrogen bonds have been shown to play an important role for the molecular mobility on amorphous surfaces as well as for the physical stabilization of ASDs. 32,33 Because of the ability of IMC to act as both a hydrogen bond acceptor (carboxylic acid and amid) and donor (carboxylic acid), the formation of hydrogen bonds between IMC molecules as well as between IMC and the acceptor groups of SP (tertiary amide and carboxylic ester) was suspected (see Figure 3 for chemical structures).…”
Section: ■ Results and Discussionmentioning
confidence: 99%